الحد من مخاطر انخفاض التدفقات النقدية التشغيلية باستخدام التحفظ المحاسبي من خلال نموذج جودة السيولة دراسة حالة مؤسسة سونطراك للفترة 2020-2022 - اشواق عريق; ايمان غربي; خولة عرعار (university of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة إلى تحليل أثر التحفظ المحاسبي على جودة السيولة ومخاطر التدفقات النقدية التشغيلية، دراسة حالة مؤسسة سوناطراك خلال الفترة 2020–2022. اعتمدت الدراسة على المنهج الوصفي وتحليل البيانات الواردة في القوائم المالية عن طريق التحليل المالي لمؤشرات السيولة، التدفقات النقدية التشغيلية والتحفظ المحاسبي بواسطةEXCEL وبرنامج الحزمة الإحصائية (SPSS, V26) لمعالجة اثر التحفظ المحاسبي عن طريق اختبار الانحدار الخطي البسيط لتحقيق اهداف الدراسة .وقد أظهرت نتائج التحليل أن التحفظ المحاسبي ساهم في خلق هوامش أمان نقدية، ووفر مستوى أعلى من الشفافية في عرض الأداء المالي، مما مكن المؤسسة من الوفاء بالتزاماتها قصيرة الأجل دون الحاجة إلى تمويل خارجي. كما تبين أن فعالية هذه السياسة ترتبط بشكل كبير بكفاءة إدارة السيولة، وأن الجمع بين الحذر المحاسبي والإدارة المالية الرشيدة يمثل استراتيجية فعالة لتعزيز الاستقرار المالي خصوصا في القطاعات الاستراتيجية مثل الطاقة. "This study aims to analyze the impact of accounting conservatism on the quality of liquidity and operational cash flow risks, through a case study of the Sonatrach company during the period 2020–2022. The study adopted a descriptive-analytical approach and analyzed data extracted from the financial statements, using financial analysis of liquidity indicators, and operating cash flows. Accounting conservatism was measured using Excel and the Statistical Package for the Social Sciences (SPSS,v26). The impact of accounting conservatism was assessed through a simple linear regression test to achieve the study's objectives. The results of the analysis showed that accounting conservatism contributed to the creation of cash safety margins and provided a higher level of transparency in presenting financial performance, which enabled the company to meet its short-term obligations without the need for external financing. The findings also indicated that the effectiveness of this policy is highly related to the efficiency of liquidity management, and that combining accounting prudence with sound financial management represents an effective strategy to enhance financial stability—particularly in strategic sectors such as energy.
ماستر
Keywords: تحفظ المحاسبي; تدفقات نقدية تشغيلية،; جودة السيولة،; مؤسسة سونطراك; Accounting Conservatism; Operating Cash Flows; Liquidity Quality; Sonatrach Company